9(7x-2)=-3x+2

Simple and best practice solution for 9(7x-2)=-3x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(7x-2)=-3x+2 equation:


Simplifying
9(7x + -2) = -3x + 2

Reorder the terms:
9(-2 + 7x) = -3x + 2
(-2 * 9 + 7x * 9) = -3x + 2
(-18 + 63x) = -3x + 2

Reorder the terms:
-18 + 63x = 2 + -3x

Solving
-18 + 63x = 2 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-18 + 63x + 3x = 2 + -3x + 3x

Combine like terms: 63x + 3x = 66x
-18 + 66x = 2 + -3x + 3x

Combine like terms: -3x + 3x = 0
-18 + 66x = 2 + 0
-18 + 66x = 2

Add '18' to each side of the equation.
-18 + 18 + 66x = 2 + 18

Combine like terms: -18 + 18 = 0
0 + 66x = 2 + 18
66x = 2 + 18

Combine like terms: 2 + 18 = 20
66x = 20

Divide each side by '66'.
x = 0.303030303

Simplifying
x = 0.303030303

See similar equations:

| -22(x-2)+44x=22(x+4)-4 | | 3(x-2)+1=-26 | | x=3g-fg | | 5h^2-9=0 | | 9(8x+11)=125 | | 40+12+0.25x=45+0.35x | | x/4-2=0 | | 9f^2-27f=0 | | -8u^2+3u+6=0 | | 3n-4n=-7 | | 3x-15=2y | | 2(3x-1)/5=5x-7/3 | | 4(1/5)=3p | | -5p+4=-2-8p-9p | | 4-2(x+5)=8x-2+4x | | x+3.9=1.8 | | x+3.9= | | x^2*y=32 | | x^3+18*x^2+72*x=1728 | | 3-(-4-6y)+7(-y+5)=-8 | | 2x+90=5c | | -15-7e=-22 | | 10m+20m^2=0 | | 15i=-75 | | .9x=15.3 | | -5.5+.56=-1.46 | | -2k+4k-5+5k= | | -17160+1859m=909m-1010 | | -.5(24+6x)=-3(x-4) | | 7/9*3/8 | | 25=51/w | | -x+27=2x+6 |

Equations solver categories